Modern Family Planning in Mali: An Analysis of the Relative Merits of Fertility Awareness Methods Versus Commodity-Based Methods - Bailey, Charles R (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Despite sustained efforts and funding by the international donors and the Malian government, the usage of family planning in Mali lags behind both regional neighbors and the international community. Only 8.2 percent of Malian women, ages 15-49 use any sort of family planning and only 6.2 percent use modern methods while total fertility rates remain virtually unchanged over the last forty years. Unmet need is currently estimated at 32 percent of women, with the majority desiring family planning to space their children better. Fertility Awareness Methods (FAMs) of family planning _ï¿½_ also known as Natural Family Planning _ï¿½_ may offer a good alternative approach to current commodity-based programs. While not new, modern FAMs have remained underfunded and underutilized in the developing world and especially in the Malian context, with a commodity-based approach dominating the interventions of governments and donor organizations. They do, however, hold some potential advantages over commodity-based contraceptives. They are natural, cheap, require no supply chain, and get around many of the problems that plague the current Malian system, including supply chain management issues, insufficient access to the distribution system by rural communities and the poor, and dependence on foreign donor funding. FAMs may also appeal to Malian women and men in areas where commodity-based contraceptives currently do not, including cultural reasons, approach to gender inequality, concern over commodity side effects, and general opposition to contraception. While greater experimentation is necessary, a FAMs-based intervention would most likely employ a train-the-trainers model and would be slow in expanding in the short term. A national organization for FAMs providers would also be necessary to maintain standards and facilitate expansion. Further research is needed to determine how best to market FAMs in a Malian context and to what level couples will commit to learn the methods.